DETEKSI NOMINAL MATA UANG DENGAN JARAK EUCLIDEAN DAN KOEFISIEN KORELASI - Gracecia, Marina; Wahyuningrum, Shinta Estri (Universitas Katolik Soegijapranata, 2017)
Recognition of money nominal is based on image grouping by reading color and specific pattern on the left side of money. The calculation of similarity is done by using euclidean distance and coefficient correlation.